2022
DOI: 10.1038/s41419-022-04842-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial oxidative phosphorylation is dispensable for survival of CD34+ chronic myeloid leukemia stem and progenitor cells

Abstract: Chronic myeloid leukemia (CML) are initiated and sustained by self-renewing malignant CD34+ stem cells. Extensive efforts have been made to reveal the metabolic signature of the leukemia stem/progenitor cells in genomic, transcriptomic, and metabolomic studies. However, very little proteomic investigation has been conducted and the mechanism regarding at what level the metabolic program was rewired remains poorly understood. Here, using label-free quantitative proteomic profiling, we compared the signature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…document SD1D-E). As previously reported, these results suggest that primary CML stem and progenitor cells of chronic phase CML patients present an aberrant proliferation with an increased metabolism to sustain high energetic demands [34]. Interestingly, pathways in DNA repair and disease, including DNA repair defects, were highly represented in both datasets, including diseases of mismatch repair and double-strand break repair linked to BRCA1/2 loss of function (Fig.…”
Section: Identification Of An Altered Metabolism and Dna Repair Trans...supporting
confidence: 80%
“…document SD1D-E). As previously reported, these results suggest that primary CML stem and progenitor cells of chronic phase CML patients present an aberrant proliferation with an increased metabolism to sustain high energetic demands [34]. Interestingly, pathways in DNA repair and disease, including DNA repair defects, were highly represented in both datasets, including diseases of mismatch repair and double-strand break repair linked to BRCA1/2 loss of function (Fig.…”
Section: Identification Of An Altered Metabolism and Dna Repair Trans...supporting
confidence: 80%
“…Metabolic analysis of stem-cell enriched CD34 + and CD34 + CD38 − and differentiated CD34 − cells from CML patients has also indicated that CML LSCs require upregulated oxidative metabolism for their survival [ 204 ]. Nonetheless, a recent study challenged this notion, claiming that OXPHOS was also upregulated, as opposed to being downregulated, in metformin-mediated killing of CML stem and progenitor cells, suggesting the dispensability of OXPHOS in CML stem and progenitor cell survival [ 205 ]. Of note for this particular study, the potentially pleiotropic and uncharacterized effects of metformin may play a role in yielding such an interpretation.…”
Section: Cell-intrinsic Signaling: Aberrant Multi-omics Circuitry Of ...mentioning
confidence: 99%
“…Metformin is a widely used antiglycemic drug for the treatment of type 2 diabetes. Preliminary studies have shown that metformin exhibits antileukemic properties [16][17][18][19]. However, the molecular mechanisms by which metformin elicits its antileukemic effects remain elusive [20].…”
Section: Introductionmentioning
confidence: 99%